Barriers to anti‐TNFalpha prescription among Italian physicians managing inflammatory bowel disease. Issue 3 (22nd April 2019) - Bezzio, Cristina; Imperatore, Nicola; Armuzzi, Alessandro; Rizzello, Fernando; Manes, Gianpiero; Bossa, Fabrizio; Calabrese, Emma; Caprioli, Flavio; Daperno, Marco; Mocciaro, Filippo; Orlando, Ambrogio; Papi, Claudio; et al.
Summary: Background: Italian physicians managing IBD patients seem to prescribe anti‐TNFalpha agents less frequently than physicians in other countries. Aims: To investigate reasons and situations that limit the use of these medications. Methods: A questionnaire was distributed to 600 physicians attending IG‐IBD events. Results: Two hundred eighty physicians (46.7%) completed the questionnaire. Most physicians (76.2%) prescribed anti‐TNFalpha every time one was needed, however, 12.6% were limited by budget, 8.1% lacked confidence, 2.2% lacked permission and 0.9% chose not to prescribe them. The limitations in using anti‐TNFalpha were: fear of side effects (39.1%), costs (38.2%), administrative/bureaucratic limitations (8.0%) and lack of staff (6.2%). The main feared side effects include: opportunistic infection (45.7%), neoplasms (25.4%), allergic reactions (12.5%), reactivation of tuberculosis (7.3%) and onset of autoimmune disease (7.3%). Physicians younger than 45 years of age and with less than 15 years of clinical experience were more likely to prescribe anti‐TNFalpha than older physicians (70.8% vs 57.1%; P = 0.022) than more experienced physicians (71.2% vs 58.9%; P = 0.033). Conclusions: The apparent underuse of anti‐TNFalpha in Italy can be attributed mainly to physicians' fears of side effects, concerns about costs and scarce familiarity with these drugs. Addressing these barriers may lead to an improvement in the quality of assistance to IBD patients.